(untitled) (Journal of Mathematical Study, 2017)
In this article we study the complex oscillation of differential polynomials generated by meromorphic solutions of the non-homogeneous linear differential equation f^(k)+A_k-1(z)f^(k-1)+...+A_1(z)f'+A_0(z)f=F, where A_i(z)(i=0,1, ...,k-1) and F are meromorphic functions of finite [p,q]-order in the complex plane.